Internalisasi Prinsip Moderasi Beragama Melalui Pendidikan Kewarganegaraan (PKn) di SMA - Heriyono Heriyono (Academicus: Journal of Teaching and Learning, 2024)
Civics education shouldn't be a dry and dull subject anymore. One such learning approach is a civics implementation strategy centered on religious moderation. Students are encouraged to investigate and evaluate diversity issues in their surroundings using the Civics learning technique, which is based on Bhineka Tunggal Ika. The concept of religious moderation is defined as a disposition of respect, tolerance, and moderation toward all forms of difference, including religious differences. Because of Indonesia's extreme diversity and the situations that lead to conflict over it, it is crucial to practice religious moderation. With civics teachers and Class X 2 students as research subjects, the purpose of this article is to clarify the significance of religious moderation guidelines through educational institutions that emphasize citizenship education (PKn) at SMA Negeri 1 Tolitoli. In order to understand a phenomenon that happens in society, this study used a qualitative descriptive research paradigm. through the use of field observations and interviewing as data collection methods. The study's findings provide an explanation for: (1) Civics education based on Bhinneka Tunggal Ika, which moderates religious learning, is beneficial in fostering national understanding and fostering conversations about diversity. Students can practice living side by side with a loving and harmonious mindset by working on projects based on Bhinneka Tunggal Ika. in any variation.